(untitled) (Leadership, Education, Personality: An Interdisciplinary Journal, ISSN: 2524-6178, 2025)
Absenteeism is one of the major human problem of Indian Industries. Employee absenteeism has a big effect on the company because it comes with a lot of charges that affect the bottom line of the company. Productivity, sustainability, profitability, competitiveness, and inter- organizational interactions are all affected.The study Entitled “Employee Absenteeism: This research helps the organization to know their current practices regarding absenteeism in any Industry. It suggests ideas to improve the business in a better prospect and result in organizational development. Employee absences are both costly and disruptive for business, and the trend has been increasing steadily over the years. Unplanned absences are mostly attributed to personal illness and family matters. Employers have been making an effort to ascertain the veracity of these ailments, provide incentives, and suggest potential remedies to lessen these absences, particularly those brought on by family matters. Stress, family obligations, illness, and other problems all have an impact on an employee's well-being, which in turn has an impact on attendance, morale, and productivity at work.